Management of Bad Loans and Their Impact on Financial Performance at KSP Kopdit Suru Pudi Koting - Wisang, Maria Dafrosa Nadyatrix; Maria Nona Dince; Konstantinus Patti Sanga (Neo Journal of economy and social humanities, 2024)
This study aims to determine the management of bad loans and their impact on financial performance at KSP Kopdit Suru Pudi Koting. Descriptive qualitative data is used in this study. The qualitative data used in this study were obtained through interviews and observations. This interview was conducted with 1 administrator, 3 employees, and 1 General Manager at KSP Kopdit Suru Pudi Koting. The data used are data on the number of bad loans and data on the impact on financial performance. The results of the study show that KSP Kopdit Suru Pudi has implemented various strategies for managing bad loans, including rescheduling, routine collection, and good communication with members. Bad loans have a significant impact on the financial performance of cooperatives, especially in terms of assets and Residual Operating Results (SHU). KSP Kopdit Suru Pudi has recorded bad loans by separating the categories of current and non-current receivables in financial statements. Provisions for receivables loss reserves are also made to anticipate potential losses due to bad loans.